A Method Study on Determination of Sediment Content in Water Samples Based on Self-made Differential Pressure Device - Xu Feifei; Wang Jian; Chen Lin; Zou Yi; Yang Chang; Li Jiande (Shuitu baochi tongbao)
[Objective] The method for quickly and accurately measuring sediment concentrations in water samples in the field based on differential pressure was studied. [Methods] Four soil types (including Lou soil, sandy soil, saline-alkali soil, and paddy soil) were chosen to prepare 11 water samples with different sediment concentrations based on the principle of pressure difference. The pressure difference between a water sample and the atmosphere was determined by using digital differential pressure meter (abbreviated as pressure difference) in order to establish the relationship between sediment concentration and pressure difference. [Results] Sediment concentration and pressure difference were linearly and positively correlated (significant at p=0.01). The method of pressure difference combined with a theoretical formula to determine sediment concentration was feasible for three of the water samples (including the Lou soil water sample, the sandy soil water sample, and the paddy soil water sample), and the absolute value of the maximum relative error was less than 15%. However, the method was not suitable for the sandy soil water sample. The absolute value of the maximum relative error in the determination of sediment concentration for the sandy soil water sample was as high as 39%. Therefore, to reduce the error, a correction equation was established by determining the pressure difference between pure water and water samples with sediment content of 500 kg/m3, and then combined with the measured pressure difference to calculate the sediment concentration. The absolute value of the maximum relative error was found to be less than 8%. [Conclusion] This method can accurately determine the sediment concentrations of water samples. It could provide a new way for conveniently determining sediment concentration in the field for soil and water conservation monitoring.